EFFECT OF G.13700A>G AND G.25783C>T IN PIT-1 GENE ON GROWTH TRAITS OF DUROC, LANDRACE, YORKSHIRE PIG - Xinxing DONG; Ziyu LIU; Xiaoyi WANG; Qiang CHEN; Gaicui BAI; Guoxiang LAN; Qian WANG; Mingli LI; Dawei YAN; Shaoxiong LU (Journal of Animal and Plant Sciences, 2023)
Pituitary specific transcription factor-1 (Pit-1) gene is responsible for pituitary development and growth hormone expression, which is considered a pivotal candidate gene for growth in pig. This study aims to detect novel single nucleotide polymorphisms (SNPs) in porcine Pit-1 gene, investigate its effect on growth traits in the Duroc, Landrace and Yorkshire pigs. Two novel polymorphisms were detected, one located in the intron 2 (g. 13700 A>G) and another located in exon 4 (g.25783 C>T) which caused an amino acid change from threonine to methionine (Thr36Met). At g.13700 A>G site, the frequency of A allele was higher than G allele in Duroc, Landrace and Yorkshire. At the g.25783 C>T site, it was remarkable differences in allelic frequencies and genotypic frequencies among the three pig breeds. This study demonstrated the significant genotype effect of Pit-1 on body weights at 70 d, age when reached 30kg, 50kg, 100kg and average daily gain from 30kg to 100kg. According to our results, the novel Pit-1 polymorphisms may be useful in pig selection as molecular markers and required in future studies.
Keywords: Pit-1; pig; growth traits; polymorphisms